Image Quality Assessment of In-House Phantom for Pediatric Computed Tomography - Prayitno, Audiena Gelung; Miftahuddin, Dafa; Hariyanto, Aditya Prayugo; Gani, Muhammad Roslan Abdul; Endarko, Endarko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
The study aimed to determine the estimated low dose and image quality of the in-house pediatric phantoms using the 128 slice CT-Scan. This study used in house pediatric phantoms (7 year). Twelve artificial cylinder targets were fabricated with diameters 3, 5, 8, and 10 mm, and CT densities -+100, -400, -750 HU. The image quality was performed using CT-Scan 128 slice (GE) with parameters of helical scanning using a low dose and standard dose and using 80 and 120 kV. For Signal noise to ratio (SNR), Contrast to Noise Ratio (CNR) were also investigated. Volumetric CT dose index (CTDIvol), Size‐Specific Dose Estimates (SSDE). The effective value of the diameter for 7-year-old was 20.15 cm. According to the study, the amount of radiation exposure measured as SSDE for in-house pediatric phantoms was found to be 3.71 mGy for low dose and 6.09 for standard dose. For image quality analysis, the low-dose CT protocol has a detection sensitivity of 100% for targets measuring > 5mm in diameter.